India's economic growth: From socialist rate of growth to Bharatiya rate of growth - Arvind Virmani (Indian Council for Research on International Economic Relations (ICRIER), 2004)
Paper reviews India's growth performance since independence. Phrases suchas "Hindu Rate of Growth," sometimes make a telling comment and expose obscureeconomic data to a wider audience, but they can just as readily obscure reality byfocussing attention on the wrong issue. There is nothing in the literature that suggeststhat this period of the "Hindu Rate of Growth" had anything to do with Hinduism per se.This paper shows that had a lot to do with the Indian version of Socialism. The 30-yearperiod from 1950-51 to 1979-80 is therefore better described as the "Indian-socialist" orperhaps "Hindu-socialist" period. The paper also identifies a truly disastrous 15-yearsub-period within this Indian-socialist period, the negative lessons of which have still notbeen fully understood or absorbed by academics, policy makers and political parties.One of the innovations in this paper is to take explicit account of rainfallvariations that play a very important role in the Indian economy. This allows us todetermine whether the Indian economy has become less dependent on the monsoons(`drought proof'). It also allows a statistically more accurate determination of thedifferent phases of Indian economic growth. The paper confirms that, what the authorhas earlier dubbed, the "Bharatiya Rate of Growth" phase began around 1980-81. Thepaper fills out the sector details of the various phases of development and the role thatgovernment and government monopoly has played in different sectors. The paper alsoexplores some of the growth puzzles in our economic history.
Keywords: N1; O1; O4; O5; P0; 330; Indian Economy; Economic Growth; Development; Phases of Growth; Socialism; Government Monopoly; Bharatiya Rate of Growth; Wirtschaftswachstum; Wirtschaftslage; Staatsmonopol; Systemtransformation; Entwicklung; Indien